2017
DOI: 10.1002/chem.201701183
|View full text |Cite
|
Sign up to set email alerts
|

Leptolyngbyolides, Cytotoxic Macrolides from the Marine Cyanobacterium Leptolyngbya sp.: Isolation, Biological Activity, and Catalytic Asymmetric Total Synthesis

Abstract: Four new macrolactones, leptolyngbyolides A-D, were isolated from the cyanobacterium Leptolyngbya sp. collected in Okinawa, Japan. The planar structures of leptolyngbyolides were determined by extensive NMR studies, although complete assignment of the absolute configuration awaited the catalytic asymmetric total synthesis of leptolyngbyolide C. The synthesis took advantage of the catalytic asymmetric thioamide-aldol reaction using copper(I) complexed with a chiral bidentate phosphine ligand to regulate two key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Leptolyngbyolides A-D 258, 259, 260, 261, were isolated from an extract derived from a Leptolyngbya species (Okinawa, Japan). 137 NMR studies enabled the planar structures of these macrolactones to be determined, while the absolute conguration for leptolyngbyolide C 260 was assigned following the asymmetric total synthesis. Furthermore, detailed biological evaluations showed that the leptolyngbyolides depolymerise lamentous F-actin.…”
Section: Cyanobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Leptolyngbyolides A-D 258, 259, 260, 261, were isolated from an extract derived from a Leptolyngbya species (Okinawa, Japan). 137 NMR studies enabled the planar structures of these macrolactones to be determined, while the absolute conguration for leptolyngbyolide C 260 was assigned following the asymmetric total synthesis. Furthermore, detailed biological evaluations showed that the leptolyngbyolides depolymerise lamentous F-actin.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…Furthermore, detailed biological evaluations showed that the leptolyngbyolides depolymerise lamentous F-actin. 137 A dichlorovinylidenephenethylamide containing NP, caracolamide A 262, was iden-tied and synthesised using a three-step process. 138 Caracolamide A 262 showed in vitro calcium inux and calciumchannel oscillation modulatory activity against murine cortical neurons at concentrations as low as 10 pM.…”
Section: Cyanobacteriamentioning
confidence: 99%
“…Thus, the biosynthesis of the samholides most likely follows a similar PKS pathway for construction of the carbon chains but with extra sugar and glyceric acid units attached as novel substituents. 2526272829303132 …”
Section: Resultsmentioning
confidence: 99%
“…Bioassay-guided fractionation of the extract of Leptolyngbya sp., collected from the coast of Itoman City in the Okinawa Prefecture (Japan), led to the separation of two macrolactones, leptolyngbyolides A-B (115-116, Figure 8), both of which showed strong growth inhibition against HeLa S 3 cells with IC 50 values of 0.1 and 0.16 µM, respectively. In addition, structure-activity relationships suggested that the sugar moiety did not affect growth-inhibitory activity (Cui et al, 2017).…”
Section: Macrocyclic Lactonesmentioning
confidence: 99%